2019
DOI: 10.1093/biolre/ioz215
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between PI3K/AKT and Hippo pathways during in vitro follicular activation and response to fragmentation and chemotherapy exposure using a mouse immature ovary model

Abstract: Understanding and control of the massive and accelerated follicular growth that occurs during in vitro culture of ovarian tissue is a crucial step toward the development of efficient culture systems that offer an attractive alternative to ovarian tissue transplantation for fertility restoration in cancer survivors. One outstanding question focuses on processes that occur prior to cryopreservation, such as tissue sectioning or chemotherapeutic treatment, might exacerbate this follicular activation. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 66 publications
3
36
0
Order By: Relevance
“…In recent years, certain novel technologies have been introduced to promote the growth and maturation of primordial follicles in vitro , becoming a promising alternative approach to fertility restoration ( Devos et al , 2020 ). In order to achieve a complete development of oocytes, a dynamic culture system that adapts to each stage of transition is required.…”
Section: In Vivo and In Vitro Follicular mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, certain novel technologies have been introduced to promote the growth and maturation of primordial follicles in vitro , becoming a promising alternative approach to fertility restoration ( Devos et al , 2020 ). In order to achieve a complete development of oocytes, a dynamic culture system that adapts to each stage of transition is required.…”
Section: In Vivo and In Vitro Follicular mentioning
confidence: 99%
“…mTORC1 promotes protein translation and ribosomal biogenesis in oocytes, by phosphorylating S6K1-rpS6 (P70 S6 kinase 1-ribosomal protein S6) and 4E-BP1 (eukaryotic translation initiation factor 4E-binding protein 1) ( Adhikari and Liu, 2010 ). Studies performed in mice and human models suggest that transient culture of ovarian tissue with mTORC1 inhibitors, such as everolimus, partially prevents spontaneous activation by limiting growing follicle counts, without impairing the ability of growing follicles to develop and synthesize hormones ( Grosbois and Demeestere, 2018 ; Grosbois et al , 2019 ; Devos et al , 2020 ).…”
Section: In Vitro Activation Of Ovarian Cortexmentioning
confidence: 99%
“…As reported, NOS/cGMP activated the PI3K/AKT pathway [55], which is involved in chemotherapy-induced follicular activation and responds to fragmentation [56]. In addition, the NOS/cGMP pathway is related to the angiotensin (HIF-1) in endothelial cells [57].…”
Section: Discussionmentioning
confidence: 75%
“…Consequently, increases in YAP nuclear translocation stimulated the expression of CCN growth factors and BIRC apoptosis inhibitors, resulting eventually in follicle growth (5, 7, 44) ( Figure 2). Furthermore, other studies confirmed that the Hippo signaling pathway works in concert with PI3K/Akt activators to accelerate primordial follicle recruitment (6,45,46). Using the animal model, several studies demonstrated thoroughly the mechanism of this intracellular signaling pathway.…”
Section: Induction Of Follicle Growth By Fragmentation Of Ovarian Cormentioning
confidence: 89%
“…Among the pathways modulating early folliculogenesis, the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway plays a crucial role in the activation of primordial follicles (4)(5)(6). Subsequent experiments suggested that the Hippo signaling pathway is also important in the development of follicles (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%